Gas turbine intercoolers: introducing nanofluids—a mini-review - Alsayegh, Ali; Ali, Naser (MDPI, 2020)
oolant is one of the main factors affecting the overall thermal performance of the intercooler for the gas turbine intercooled cycle. The thermal conductivity of conventional coolants, such as water, is relatively low when compared to solid conducting materials, and therefore can hinder the progress towards achieving a compact and highly effective intercooler. Nanofluids are advanced types of working fluids that contain dispersed nanoparticles in conventional basefluids, and as such possess superior thermal conductivity compared to their counterparts. In this paper, a short review on the effect of different nanofluids on the thermal performance of gas turbines intercoolers is presented for the first time. Firstly, this work reviews the different designs of intercoolers used in gas turbines intercooled cycles. Then, it explains the different types of nanofluids and their fabrication processes. The effective parameters, such as physical stability, thermal conductivity, and viscosity are also highlighted and discussed. Furthermore, the level of enhancement in the performance of intercoolers utilizing nanofluids is demonstrated and evaluated. Lastly, the current challenges and future research directions in this field are provided.
Keywords: heat exchanger; suspension; stability; thermophysical properties; working fluid